A Review on Gas‐Liquid Reactions in Light Oil Sweetening: Kinetics and Reactor Design Aspects. Issue 5 (1st October 2014) - Ganguly, Sudip K.; Varun, Neetu; Kumar, Sunil; Khatri, Praveen K.; Jain, Suman L.; Garg, Madhukar O.; Pellegrini, Laura A.
Abstract Thiols in liquefied petroleum gas are undesirable due to their foul odor and corrosive nature. The process of removing these thiols is termed as sweetening. Metal phthalocyanines are reported to be the most effective sweetening catalyst. However, the solubility of metal phthalocyanine is low in aqueous medium. Thus, in an effort to further improve upon the existing catalysts, a novel cobalt phthalocyanine sulfonamide catalyst was developed. Laboratory and commercial evaluation of this catalyst showed enhanced activity as compared to a commercial catalyst with comparable stability. With proven higher activity, comparable stability, design of grass root oxidizer using this catalyst is the next step. Design of oxidizers for an extractive sweetening process based on this catalyst in grass root refineries requires a rigorous kinetic model. The paper reviews the literature on sweetening kinetics and focuses on the concepts of design of laboratory reactors for reaction kinetics studies for such gas‐liquid reactions. Laboratory reactor systems can be useful for accurate estimation of kinetic parameters which can then be used to design industrial reactors and predict their performance.